The Impact of Digital Taxation Implementation and Taxpayer Knowledge on Tax Revenue Obstacles, Moderated by Incentive Policy - Susilowati, Ani; Mappanyukki, Ratna (Bina Nusantara University, 2023)
The COVID-19 pandemic’s worsening economic conditions increased obstacles in tax revenue. The obstacles that arise during the tax collection process take the form of tax evasion and tax avoidance by citizens. The research aimed to empirically prove the impact of digital taxation, taxpayer knowledge, and tax incentive policies during the COVID-19 pandemic, with tax obstacles as the dependent variable. The comprehensive discussion of the relationship between all variables in the research is a novelty of previous studies, which were carried out partially. The research population comprised corporate taxpayers in Jakarta, with a sample of 50 corporate taxpayers selected as the respondents usingconvenience sampling techniques. The data analysis technique used was quantitative, utilizing PLS-SEM (Partial Least Squares-Structural Equation Model). The research results indicate that implementing digital taxation and taxpayer knowledge significantly and negatively affect tax revenue obstacles. Moreover, tax incentive policies during the COVID-19 pandemic were a quasi-moderator variable that strengthens tax obstacles’ adverse and significant effects. The research implications highlighted the crucial role of digital taxation and taxpayer knowledge in mitigating obstacles to tax revenue. The findings suggest that effectively implementing digital taxation measures and enhancing taxpayer knowledge can significantly reduce tax evasion and avoidance hindrances.